1985
DOI: 10.1016/0300-9629(85)90442-6
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation of the cane toad, Bufo marinus, in salt water

Abstract: Abstract-1. Adult cane toads, B. marinus, survived in salinities up to 40% sea-water (SW).2. Pre-exposure to 30, then 40% SW, increased the survival time of toads in 50% SW. 3. Plasma from toads acclimated to salt water is hyperosmotic to the environment -a result of increased plasma sodium, chloride and urea concentrations.4. When toads were placed in tap-water and 20% SW, all significant changes to plasma sodium, chloride, urea and osmotic pressure occurred within the first 2 days of exposure.5. When toads w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Probably, tadpoles may stay and metamorphose mostly in microhabitats (e.g., small, water-filled depressions in hummocks towards the base of Pterocarpus' trees) without getting into larger bodies of water, which may explain the scarcity of tadpoles capture by dip netting along the inlandto-coast salinity gradient. Bufo marinus is considered a euryhaline amphibian (Liggins and Grigg, 1985) and commonly breed in sites frequently used by the crab-eating frog, Fejervarya cancrivora (Anura: Ranidae), the most euryhaline frog that occurs throughout Southeast Asia (Hogarth, 1999;D.S. Rabor, 1952cited by Lever, 2003.…”
Section: Discussionmentioning
confidence: 98%
“…Probably, tadpoles may stay and metamorphose mostly in microhabitats (e.g., small, water-filled depressions in hummocks towards the base of Pterocarpus' trees) without getting into larger bodies of water, which may explain the scarcity of tadpoles capture by dip netting along the inlandto-coast salinity gradient. Bufo marinus is considered a euryhaline amphibian (Liggins and Grigg, 1985) and commonly breed in sites frequently used by the crab-eating frog, Fejervarya cancrivora (Anura: Ranidae), the most euryhaline frog that occurs throughout Southeast Asia (Hogarth, 1999;D.S. Rabor, 1952cited by Lever, 2003.…”
Section: Discussionmentioning
confidence: 98%
“…Similar effects were noted among tadpoles of the same species which were observed to cope better with high salinities than those initially grown in a low saline environment (Gordon et al 1961). Liggins and Grigg (1985) observed that adult B. marinus survived up to 1.4 per cent NaCl while acclimated individuals survived salinities of 1.75 per cent. Dunson (1977) observed that when R. cancrivora were acclimatized to high temperatures, individuals were better able to cope with saline environments when temperatures were further elevated.…”
Section: Salinitymentioning
confidence: 96%
“…Published data on Australian frogs are limited to investigations of adult B. marinus. Van Beurden and Grigg (1980) recorded this species in brackish water while Liggins and Grigg (1985) observed that adults were able to tolerate salinities up to 1.4 per cent. Overseas studies indicate that difference in susceptibility to salinity is common both within (e.g., Beebee 1985;Christman 1971), and between, species (e.g., Bentley and Schmidt-Neilsen 1971;Munsey 1972).…”
Section: Salinitymentioning
confidence: 99%
“…comm.). Adult cane toads can survive in 40% seawater (Liggins & Grigg, 1985), allowing them to inhabit the lower reaches of the Daly River.…”
Section: Study Areamentioning
confidence: 99%